Partisipasi Masyarakat dalam Musrenbang Daerah di Kecamatan Baranti Kabupaten Sidenreng Rappang - Heriyanti Zain (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
This research came from a process when a member of society as individual or social group directly affected and took a role in planning, executing, and monitoring people’s life driven policies. Therefore the society needed to give more participation in regional development plan conference (we call it Musrenbang). Regional development plan conference held a regional forum consisting all district leaders. District leader in charge was held responsible to organize and coordinated by region leader to invite all social level of society to participate. This research was held in Baranti district which populated by fifty-two (52) people, all accounted as research’s sample using total sampling method. Researcher used observation, interview, questionnaire, and literature study method to collect data, and the descriptive-qualitative method to analyze them. The following result consisted of: development plan conference’s participation held on target by scoring 53,85%; people’s idea aspirated on conference was less aspirated by scoring 65,38%; the importance of the conference to develop Baranti district was high by scoring 67,31%; people’s satisfaction given the regional conference’s result was less satisfied by scoring 53,85%; people’s evaluation towards regional conference’s implementation was satisfactory by scoring 79,92%; and the implementation of regional conference to fulfil people’s needs was quite good by scoring 46,15%. The influencing factors consisted of: positive effect from regional conference’s implementation in district development was quite positive by scoring 53,85%; the intensity of people and government attending the conference was not good enough by scoring 61,54%; people’s participation in the conference’s decision making was quite participative by scoring 50%; and the uniformity between the conference’s result and regional mid-term development plans was less appropriate by scoring 82,69%.